Correla????o das caracter??sticas do arco plantar de idosas sedent??rias com o risco de queda - Brescovici, Telma Elisa (2016)
Introduction: The foot plantar arch is essential to maintain a correct body biomechanics. However, due to aging, changes occur in the foot anatomical and physiological structures, which can hinder ambulation and interfere in the individual's quality of life. It is important to remind that currently one of the main concerns related especially to the elderly is the occurrence of falls. Objective: This study aimed at determining whether there is correlation between the plantar arch type and the risk of falls in sedentary elderly women. Methods: A cross-sectional, quantitative study with 47 elderly women between 60-69 years old, attending a support group called Programa Idade Viva in the municipality of Barreiras/BA. It was used the Functional Reach Test (FRT) and the Timed Get Up and Go (TUG Test) to evaluate the balance, along with the plantar evaluation test through a Pedigraph. Results: The results showed that among the subjects who presented risk of falls through the Functional Reach Test (FRT), most of them had an intermediary type of plantar arch. According to the TUG test, most elderly were considered fragile (with low risk of falling), and none had increased risk of falling. Conclusion: There was no significant correlation between the plantar arch and the risk of falls, it is suggested further research with a larger number of subjects to identify the influence of the plantar arch on the elderly balance.